Quality of Professional Psychologist Training in Online Space - Oleksii Nalyvaiko; Kseniia Lykhoshvai (Educational Challenges)
The article is devoted to the definition of the basic provisions of training psychologists in the conditions of forced distance learning. The purpose of the study is to analyze the main qualities that a future psychologist should have, and to consider the impact of online learning (forced distance learning) on their quality and formation. The main objectives include: analyze theoretical framework of modern training of a psychologist; analyze the role of digital and online technologies in teaching future psychologists; analyze the answers given by student psychologists during a survey aimed at determining the role of online learning; propose recommendations for improving the learning process of future psychologists in a distance / blended learning.